"Subben׳s checklist" and the assessment of articles in mathematical optimization/operations research: In memoriam of Subhash C. Narula. (July 2016) - Larsson, Torbjörn; Patriksson, Michael
Abstract: Excellent guides on academic writing and presentation in science in general, and in mathematics and computer science in particular, do abound (see, for example, Refs.[1–8], while guides on the assessment of the results of academic writing are rather more scarce. This short article presents two itemized lists that may be helping hands during the assessment of a scientific article in the field of mathematical optimization and operations research—be it your own, a work by a Master or PhD student of yours, or even a manuscript that you are refereeing for a scientific journal or conference proceedings volume. The first list—"Subben׳s checklist"—describes necessary ingredients of a complete article. The second list provides criteria for assessing the quality and scientific value of an article. Abstract : Highlights: Subben׳s checklist provides a compact and convenient means to assess whether a manuscript in the field of the mathematical sciences is complete, in the sense that the manuscript covers those items that are considered necessary, from a clear motivation for the research described, through a clear and lucid description of the work, to a discussion on the work׳s consequences, uses, and possible future improvements and generalizations. The second highlight is the second list–of criteria by which a scientific work can be evaluated, in terms of, for example, scientific height and depth, whether it integrates a lot of previous knowledge, etcetera.